Effect of Trans Glutaminase and Glucose Oxidase Addition on Rheological and Baking Characteristics of Wheat and Oat composite flour - Sardar, Sayran; Zainulabideen, Mohammed Wajeeh (Sulaimani Journal for Pure and Applied Sciences, 2018)
The effect of Transglutaminase (TGase) and Glucose oxidase (GOase) on white, wheat, oat and their composite flours were studied. The chemical content significantly differed among the treatments, especially protein percentages which was ranged between 9.58±0.52 for white flour and 12.67±0.10 for Aras flour. Substitution 30% of white and Aras flours by oat flour caused increasing of all Amylograph parameters while addition of TGase and GOase highly decreased the breakdown of viscosity during stability of paste heating. In the same manner addition, the both enzymes increased Farinograph water absorption and somewhat stability time. However, the effect of two enzymes on the other Farinograph parameters depended on the quality of the studied flour. Addition of TGase and GOase, in general, improved loaf specific volume and volume to protein, in addition to their improving to loaf curst color and crust uniformity. This study was carried out at University of Sulaimani / Faculty of Agricultural Sciences –Food Science department, to study the effect of transglutaminase (TGase) and Glucose oxidase (GOase) on dough rheology and baking test of wheat (Triticum aestivum L., type; Aras cultivar) and Oat (Avena sativa L.) and then the results were compared with studied wheat white flours.